Evidence of the potential benefits of digital technology integration in Asian agronomy and forestry: A systematic review - Zulfadli Hazim, Zul Azlan; Syahrul Nizam, Junaini; Noor Alamshah, Bolhassan (Elsevier, 2024)
CONTEXT The agronomy–livestock–forestry nexus is critical as it influences ecosystem services, food production, and land use. Asia, a diverse and technologically dynamic region, faces disparities in agronomy tech adoption. Studies emphasize agronomy and forestry's pivotal role in determining livelihoods in the region. Challenges like rising food demand, land scarcity, climate change, and biodiversity loss require innovative solutions. Digital technologies offer enhanced productivity, sustainability, and resource management opportunities, defining the era of smart agriculture and forestry.